Local Stabilization of Hypoxia-Inducible Factor-1α Controls Intestinal Inflammation via Enhanced Gut Barrier Function and Immune Regulation - Kim, Young-In; Yi, Eun-Je; Kim, Young-Dae; Lee, A Reum; Chung, Jiwoung; Ha, Hae Chan; Cho, Joong Myung; Kim, Seong-Ryeol; Ko, Hyun-Jeong; Cheon, Jae-Hee; Hong, Yong Rae; Chang, Sun-Young (Frontiers in Immunology, 2021)
Intestinal epithelial cells are adapted in mucosal hypoxia and hypoxia-inducible factors in these cells can fortify barrier integrity to support mucosal tissue healing. Here we investigated whether hypoxia-related pathways could be proposed as potential therapeutic targets for inflammatory bowel disease. We developed a novel hypoxia-inducible factor (HIF) prolyl hydroxylase inhibitor, CG-598 which stabilized HIF-1a in the gut tissue. Treatment of CG-598 did not affect extra-intestinal organs or cause any significant adverse effects such as erythropoiesis. In the experimental murine colitis model, CG-598 ameliorated intestinal inflammation with reduction of inflammatory lesions and pro-inflammatory cytokines. CG-598 treatment fortified barrier function by increasing the expression of intestinal trefoil factor, CD73, E-cadherin and mucin. Also, IL-10 and IL-22 were induced from lamina propria CD4+ T-cells. The effectiveness of CG-598 was comparable to other immunosuppressive therapeutics such as TNF-blockers or JAK inhibitors. These results suggest that CG-598 could be a promising therapeutic candidate to treat inflammatory bowel disease.